Cumplimiento de cuota de empleo de las personas con discapacidad en las entidades públicas de la provincia de Maynas 2020 - Vargas Sosa, Edson Paulo (2023)
The purpose of this study was to determine compliance with the employment quota of persons with disabilities in public entities in the province of Maynas during 2020, fair measures regulated in the General Law of Persons with Disabilities. The research had a non-experimental, descriptive, cross-sectional, quantitative approach. The sample consisted of 37 people with disabilities, and a structured questionnaire with 22 items and two answers was used as a data collection instrument. The most relevant results show that 67.6% of those evaluated know about some law that defends their rights, as well as 33.4% do not know about any law, likewise 51.4% know about the employment quota for people with disabilities. Likewise, those evaluated indicate that the state entities do not have a work environment suitable for them. On the other hand, 86.5% also mentioned that public entities do not comply with the employment quota established by law and 73% of the sample studied are not affiliated to any union. The study concludes that the public institutions of the Province of Maynas do not comply with the employment quota indicated in the General Law for Persons with Disabilities.